The Perception of Nonverbal Behavior in the Career Interview. - Raffler-Engel, Walburga von (Pragmatics & beyond, 1983)
Walburga von Raffler-Engel takes a novel approach to compiling information about doctor-patient communication. She has surveyed popular literature around the world to gain a grass-roots' perception of this relationship in various cultures. Most of the contributions are by practicing physicians, illustrating reflections on doctor-patient communication from both the physician's as well as the patient's points of view. A variety of disciplines are involved in the study of this subject, such as discourse analysis, non-verbal communication, psychology, sociology, education, etc.